Prevalence of chondrocalcinosis in a Mexican tertiary care institution of musculoskeletal disorders - De la Garza-Montaño, Paloma; Pineda, Carlos; Lozada-Pérez, Carlos Alberto; Camargo-Ibarias, Katia; González-Hernández, María Fernanda; Avila-Luna, Alberto; Ruiz-De la Garza, Gerardo A.; Bertolazzi, Chiara; Clavijo-Cornejo, Denise; Gutierrez, Marwin (Clinical rheumatology, 2019)
Introduction/objectives The prevalence of chondrocalcinosis (CC) was reported as variable according to the geographic populations. However, there are no data regarding its prevalence in Mexico. Thus, we decided to investigate the Mexican prevalence of CC in a cohort of patients from a tertiary health care institution. Methods A retrospective analysis of radiographs of knees and wrists from our institution was performed. Inclusion criteria included patients > 50 years old having radiographs of knees and wrists. Radiographic presence of CC was classified according to a dichotomous evaluation assayed by two rheumatologists experts on the area. Results A total of 3.350 radiographs from 1.602 patients were evaluated. Forty-seven patients showed calcifications in at least one knee or wrist for an overall prevalence of 3%, of which 23.4% were men and 76.6% women. The knee was more commonly affected than the wrist (85.1% and 14.9% respectively). The prevalence according to gender was 2.9% in women, whereas, it was 3.2% in men. Only two patients (4.3%) showed a contemporaneous presence of CC in both hands and both knees. At knee level, the prevalence was 2.7%, whereas at the wrist, we reported a prevalence of 4.9%. Conclusions The prevalence of CC for Mexican population had not been reported so far. This a starting point to break the silence and encourage the knowledge of how this disease is associated with possible risk factors in Mexican population. Key Points • The prevalence of chondrocalcinosis in Mexico was 3%. • The prevalence of knee chondrocalcinosis increases according to the age in women’s. • The nixtamalized meals could be a protective factor for CC in Mexican population.